Analysis of Creative Entrepreneurship Strategy for Sustainable Innovation in the Digitalization Era - Nuril Hikmah; Adisty Riska Hardianti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This study aims to analyze the challenges and opportunities faced by creative entrepreneurs in utilizing digital technology, with an emphasis on its impact on economic and social growth. This study was conducted using a qualitative method through a case study approach on a number of creative entrepreneurs in Indonesia and abroad, both successful and unsuccessful. The results of the study revealed that digital technology plays an important role in expanding market reach and increasing operational efficiency, which in turn creates new, more adaptive business models. The findings of this study indicate that continuous innovation and cross-disciplinary collaboration are key factors in producing competitive products or services in the global market. Creative entrepreneurs who are able to innovate consistently tend to have an advantage in attracting consumer interest and maintaining sustainable business growth. As a recommendation, this study proposes the need for support from the government and the private sector in the form of training and regulations that better support the growth of digital-based creative entrepreneurship in Indonesia.